Environmental conditions and carbonate chemistry variability influencing coral reef composition along the Pacific coast of Costa Rica - Sánchez-Noguera, Celeste; Lange, Ines D.; Cortés, Jorge; Jiménez, Carlos; Wild, Christian; Rixen, Tim (Frontiers in Marine Science, 2025)
Coral reef development is influenced by a wide variety of factors, including temperature, salinity, nutrient concentrations, and carbonate chemistry. Studies focusing on physicochemical drivers of coral reef distribution and composition in the Eastern Tropical Pacific (ETP) are scarce, and carbonate chemistry and nutrient data for this region are limited. This study measured coral reef composition and physicochemical parameters along the Pacific coast of Costa Rica, over a one-year period at three locations: Santa Elena and Matapalo in the north, and Parque Nacional Marino Ballena in the south. Our results show high seasonal and spatial variability of physicochemical conditions with significant differences mainly explained by inorganic nutrient concentrations, with driving processes also having a strong influence on the variability of carbonate chemistry parameters. Coastal upwelling is the main driver of the seasonal variability in Santa Elena. Comparison of seasonal dissimilarity within locations confirms the presence of a geographical gradient, with stronger influence of the upwelling in Santa Elena relative to Matapalo, where several parameters displayed a lower seasonality and a carbonate system that supports reef development throughout the year. Conversely, in Marino Ballena the river discharges during rainy season exerted a strong control on the seasonal variability. The integrated analysis of coral reef composition and physicochemical parameters suggests that in addition to inorganic nutrients carbonate chemistry also plays a key role in coral distribution. Analyzing the spatial distribution of the main reef builders provides insights into the species-specific tolerance to varying conditions. Pavona clavus is widely distributed in both the northern and southern locations, suggesting that this massive coral is very tolerant to the high variability of physicochemical conditions. The dominant corals in the north (Pavona gigantea and Pocillopora spp.) are highly tolerant to nutrient-enriched cold waters with low aragonite saturation, while one of the main reef-builders in southern locations (Porites cf. lobata) cope better with low salinity, low aragonite saturation and low light intensity caused by river discharges. Understanding the preferences of individual coral species at our study locations can shed light on the environmental factors driving coral reef distribution in other locations of the ETP.